P1595 Prognostic role of late gadolinium enhancement for sudden cardiac death risk in non-ischemic dilated cardiomyopathy. (17th January 2020) - Rodriguez Sanchez, I; Onaindia, J J; Gomez, V; Aguirre Larrakoetxea, U; Velasco, S; Urkullu, A; Ullate, A; Capelastegui, A; Astigarraga, E; Florido, J; Natividad, R; Garcia Ibarrondo, N; et al.
Abstract: OBJECTIVES: to evaluate the prognosis role of late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (cMRI) in patients with non-ischemic dilated cardiomyopathy (NIDM). BACKGROUND: Risk stratification in NIDM needs to be improved. METHODS: We included 210 patients with NIDM and cMRI from 2005 to 2018 in our study population. Outcomes were retrospectively assessed by medical records. The pattern of LGE was classified as mid-wall, sub-epicardial, or both patterns. Primary endpoint was sudden cardiac death (SCD) or aborted SCD. Secondary endpoints were global mortality and a composite endpoint of cardiovascular mortality and heart failure hospitalization. Demographic and clinical parameters were also evaluated. Patients with LGE (LGE+) were more likely to be male (80, 6% vs 66, 7%, p= 0, 03). No significant differences were observed between LGE+ and LGE- patients in comorbidities, NYHA class, left ventricular ejection fraction (LVEF), or neurohormonal treatment. RESULTS: Of 210 patients (71, 4% men, median age 59, 8 years) with a median follow up of 5, 6 years (3, 24-8, 15), 72 patients (34, 3%) had non ischemic LGE (LGE+) on cMRI. Mean left ventricular ejection fraction (LVEF) was 34%. SCD or aborted SCD occurred in 11 patients (5, 2%): 6 patients (9, 5%) with LGE+ vs 5 patients (4, 07 %) of LGE- (p = 0, 19). Patients with LGE+ had a higher risk for the composite endpoint (cardiovascular mortality and heart failure hospitalization): OR 2, 45, confidence interval (CI): 1, 16-5, 17, (p = 0, 02). LGE presence was not associated with global mortality. The subepicardial pattern of LGE was associated with SCD or aborted SCD. 3 out of 11 patients (27%), with subepicardial pattern of LGE suffered from SCD or aborted SCD (p= 0, 01). CONCLUSIONS: In our cohort of 210 patients with NIDM, LGE was not significatively associated with SCD or aborted SCD, probably because of a low event rate (5, 2%) in a relatively small and well treated population, despite a long follow-up (5, 6 years). On the other hand, LGE presence was associated with a higher risk for the composite endpoint of cardiovascular mortality and heart failure hospitalization. Finally, the subepicardial pattern of LGE identified a group of patients at high risk of SCD and aborted SCD.